Simulace zkoušky stability vozidla - Budka, Josef; Budka Josef (České vysoké učení technické v Praze, 2016)
Tato práce se zabývá stabilitou vozidla a simulací zkoušky stability vozidla. Nejprve popisuje obecně stabilitu a pohybové rovnice. Dále seznamuje s provedenou zkouškou stability vozidla s pohyblivým těžištěm na Fakultě dopravní ČVUT a řeší simulaci tohoto jevu v softwaru Adams. V závěru porovnává naměřené hodnoty a hodnoty ze simulace.

This thesis focuses on the stability of a vehicle and the simulated vehicle stability test. It initially describes both, the basis of stability and the motion-calculation equations. Later, the thesis introduces the results of previously performed vehicle stability test with a moving center of gravity at the faculty of transportation sciences CTU and solves the simulation of this phenomenon using the Adams software. Lastly, the thesis compares the measured values and the values generated during the simulation.
Simulation of vehicle stability test
Keywords: Dynamika vozidla, stabilita, zkoušení, zkouška stability, těžiště, simulace, Adams, Adams/Car, pohyblivé těžiště.; Vehicle dynamics, stability, testing, stability test, center of gravity, simulation, Adams, Adams/Car, movable center of gravity.